UPAYA GURU DALAM MENANAMKAN SIKAP TOLERANSI SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS III SDN 27 ANAK AIR - Septiani, Ratih; Atri Waldi; Yesi Anita; Gita Rahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the teacher's efforts to instill an attitude of tolerance during Pancasila Education lessons in the third-grade class at SDN 27 Anak Air. The study employs a qualitative research design with a descriptive approach, utilizing observation, interviews, and documentation as data collection techniques. This qualitative approach seeks to gather comprehensive information regarding the teacher's efforts to foster tolerance among students within the context of Pancasila Education. The findings indicate that the teacher instills tolerance by integrating the value into every stage of the lesson, from the opening to the closing. Specific strategies include modeling tolerant behavior, forming heterogeneous study groups, facilitating student discussions, encouraging respect for differing opinions, treating students fairly, using inclusive language, and conducting value-based reflection and conflict resolution when disputes arise among students.